Efficacy of lumacaftor-ivacaftor for the treatment of cystic fibrosis patients homozygous for the F508del-CFTR mutation. Issue 3 (3rd May 2016) - Cholon, Deborah M.; Esther, Charles R.; Gentzsch, Martina
ABSTRACT: Cystic fibrosis (CF) results from mutations in the CF transmembrane conductance regulator (CFTR) gene, which codes for the CFTR channel protein. The most common mutation in CF is F508del, which produces a misfolded protein with diminished channel activity. The development of small-molecule CFTR-modulator compounds offers an exciting and novel approach for pharmacological treatment of CF. The corrector lumacaftor helps rescue F508del-CFTR to the cell surface, and potentiator ivacaftor increases F508del-CFTR channel activity. The combination of lumacaftor-ivacaftor (Vertex Pharmaceuticals Incorporated) represents the first FDA-approved therapy for CF patients with two copies of the F508del mutation. Although this combination therapy is the first treatment to directly target the F508del-CFTR mutation, patients taking this drug displayed only modest improvements in lung function. This article summarizes recent data from clinical trials and research discoveries relating to the lumacaftor-ivacaftor treatment, and considers options for identifying future therapies that will be most efficacious for all CF patients.